Learning Relevance IPS against Student Social Interaction in Multicultural Scope on Junior High School Remaja Parakan - Sari, Amalia Devita; Raharjo, Tri Joko; Utomo, Cahyo Budi (JESS (Journal of Educational Social Studies), 2017)
Remaja Parakan Junior High School is one of small symbols of multicultural which has javanase and tionghoa ethnic. In order to create good interaction, it should be known how social science study is being delivered by social study teacher can effect in creating social interaction to students in multicultural environment. The aim of this study is to analyze The relevance of social science study to studentâ€™s social interaction in multicultural environment at Remaja Parakan Junior High School, also to know the role of social science teacher and her role in school environment in delivering social science learning. The research leads to how social science learning manages the knowledge of the students abaout the kinds of differentiation in social environment. The method of the research used qualitative research. The result is Remaja Parakan Junior High School maintains the multicultural which is similar to Indonesia motto â€œBhinekka Tunggal Ikaâ€ that means although being difference but stay equal. The difference in religion, ethnic, social and culture have the same position. The role of school in giving habitual to the students to have multicultural mind in Remaja Parakan Junior High School can be seen in many school activities whether indoor learning or outdoor learning.